«Donna d’effetto non lo sarò mai». De-erotizzazione e mascheramento nell’immagine divistica di Rita Pavone sulla stampa giovanile nella seconda parte degli anni Sessanta (Il caso «Giovani») (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The following paper aims at:1) Implementing Richard Dyer’s concept of “structured polysemy” (1979) to map the variety of conflicting images that emerge of Rita Pavone through films and youth magazines; 2) Describing the de-sexualization process that Pavone’s star image undergoes in youth magazines and how it affects her on-screen image (paying particular attention to the column “Il mio diario”, that she personally curated for the magazine «Giovani»);3) Evaluating these processes within the broader de-sexualization phenomenon that characterized specific youth and Italian pop music scenes in the years leading up to 1968.The following paper aims at 1) Implementing Richard Dyer’s concept of structured polysemy (1979) to map the variety of conflicting images that emerge of Rita Pavone through films and youth magazines; 2) Describing the de-sexualization process that Pavone’s star image undergoes in youth magazines and how it affects her on-screen image (paying particular attention to the column Il mio diario, that she personally curated for the magazine Giovani); 3) Evaluating these processes within the broader de-sexualization phenomenon that characterized specific youth and Italian pop music scenes in the years leading up to 1968.